Antioxidant and protective effects of methanolic Solanum nigrum leaf extract against CCl4-induced hepatotoxicity and renotoxicity in albino rats - Taher Issa Shailabi; Ahmed Saeed Kabbashi; Osama Hussein Aldeeb; Eman Salah Basheer; Rehab Aeyad Gumaa; Ebtihal Jebriel Younes; Retaj Fawzi Mohammed; Amar Mohamed Ismail (Open Veterinary Journal)
Background: There is growing interest in natural antioxidants, particularly Solanum nigrum (S. nigrum), because of their potential to protect against oxidative stress-induced organ damage and their intriguing historical use in treating various medical conditions.